THE SOCIETY NEED IN RATIONAL INTELLECTUAL USE TO PROVIDE FUNCTIONING AND DYNAMIC DEVELOPMENT (Regional aspects of productive forces development of Ukraine, 2019)
The article deals with the works of domestic scientists who have researched the problems of creation, management and intellectual use. The views of scientists are focused on understanding the management of processes of intellectual use, the study of intellectual resources in the knowledge economy, the study of aspects of valuation of intellectual capital and the influence of factors on its management mechanism, the establishment of the place of intellectual assets in the national innovation system.The purpose of the research is based on the development of ways to manage the process of intellectual use in the domestic knowledge economy. This will maximize the efficiency of the use of individual, corporate and state intellectual capital.It has been established that developed countries implement and implement knowledge management programs that help achieve business efficiency, society and the state. Declining government funding for higher education institutions is hampering the creation of new knowledge, leading to lower revenues for the business sector and budget revenues.State levers in the field of education that can improve its quality and prevent the migration of knowledge are revealed. At the state level, education reforms should be implemented that focus on the quality of the teaching staff of higher education institutions.Illuminated tools for managing knowledge based on innovation and serving as intangible assets. Models characterizing the influence of knowledge on financial and economic activity have been formed. These models reflect the process of exchanging intellectual resources between partners.A cyclic-conectic model of the application of new knowledge for the purpose of their commercialization or capitalization is proposed. It is noted that knowledge as a resource is dual in nature and requires a specific approach to assessment and management. A price-margin model of intellectual use has been developed that includes certain components that affect the size of the margin.